2020
DOI: 10.3390/ijerph17103701
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Chronotype, Physical Activity and the Estimated Risk of Dementia in Community-Dwelling Older Adults

Abstract: Our study examined the association between chronotype, daily physical activity, and the estimated risk of dementia in 170 community-dwelling older adults. Chronotype was assessed with the Horne–Östberg Morningness–Eveningness Questionnaire (MEQ). Daily physical activity (of over 3 METs) was measured with a tri-axial accelerometer. The Korean version of the Mini-Mental State Examination (K-MMSE) was used to measure the estimated risk of dementia. The evening chronotype, low daily physical activity, and dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…Sarcopenia-related factors, such as muscle mass, grip strength, and physical function, may be influenced by the MEQ scores and physical activity. Morningness has been shown to have higher daily physical activity than eveningness (17) and increased physical activity may result in higher muscle mass (18). However, in the present study, sarcopenia-related factors in healthy and obese subjects were not associated with the MEQ score or physical activity.…”
Section: Relationship Between Pattern and Timing Of Protein Intake And Sarcopenia-related Factorscontrasting
confidence: 74%
See 1 more Smart Citation
“…Sarcopenia-related factors, such as muscle mass, grip strength, and physical function, may be influenced by the MEQ scores and physical activity. Morningness has been shown to have higher daily physical activity than eveningness (17) and increased physical activity may result in higher muscle mass (18). However, in the present study, sarcopenia-related factors in healthy and obese subjects were not associated with the MEQ score or physical activity.…”
Section: Relationship Between Pattern and Timing Of Protein Intake And Sarcopenia-related Factorscontrasting
confidence: 74%
“…In the subjects requiring support in this study, we were not able to examine the effect of physical activity on muscle mass and strength because we were not able to sufficiently measure physical activity meters. However, it has been shown that the amount of daily physical activity is higher in morning-type people (17), and it is possible that the muscle Values are expressed as the mean ± standard error. † P < 0.05, compared to EPRO (Mann-Whitney).…”
Section: Differences In Protein Intake Balance and Sarcopenia-related Factors In Obese People And Those Requiring Supportmentioning
confidence: 99%
“…In terms of marital satisfaction, chronotype also has a predictive role, with the morning chronotype having higher marital satisfaction ( Shareh and Eshaghi Sani, 2019 ). Chronotype has been associated with nervous system diseases such as dementia, fibromyalgia ( Thapa et al, 2020 ; Turkoglu and Selvi, 2020 ), and epilepsy ( Manni et al, 2016 ), or physiological factors such as adiposity ( Cespedes Feliciano et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, its exact etiology and pathogenesis are still unclear. AD is the fourth largest cause of death in older adults after cancer, heart disease, and cerebrovascular disease [ 3, 4 ], whose single most important non-modifiable risk factor is age [ 5 ]. The increasing incidence of AD and the huge associated social and economic burden have stimulated research into multiple protective factors to prevent the occurrence and development of this neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%